1991
DOI: 10.1104/pp.96.4.1354
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Macerase, Oxalic Acid, and EGTA on Deep Supercooling and Pit Membrane Structure of Xylem Parenchyma of Peach

Abstract: The object of this study was to determine if calcium crosslinking of pectin In the pit membrane of xylem parenchyma restricts water movement which results in deep supercooling. Current year shoots of 'Loring' peach (Prunus perska) were infiltrated with oxalic acid or EGTA solutions for 24 or 48 hours and then either prepared for ultrastructural analysis or subjected to differential thermal analysis. The effect of 0.25 to 1.0% pectinase (weight/volume) on deep supercooling was also investigated. The use of 5 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…In case of freeze avoidance, soluble sugars may help to inhibit the formation of ice crystals and to stabilize the plasmatic membrane. Furthermore, the integrity of the amorphous layer and its pectin composition are important for the ability of parenchyma cells to undergo supercooling (Wisniewski and Davis 1989 ;Wisniewski et al 1991b ).…”
Section: The Role Of Sapwood Nsc At the Whole Plant Levelmentioning
confidence: 99%
“…In case of freeze avoidance, soluble sugars may help to inhibit the formation of ice crystals and to stabilize the plasmatic membrane. Furthermore, the integrity of the amorphous layer and its pectin composition are important for the ability of parenchyma cells to undergo supercooling (Wisniewski and Davis 1989 ;Wisniewski et al 1991b ).…”
Section: The Role Of Sapwood Nsc At the Whole Plant Levelmentioning
confidence: 99%
“…It has been hypothesized that XPCs of trees can supercool to -40°C as isolated water droplets because the protoplasts without heterogeneous ice nucleators are physically isolated from effects of extracellular ice by the presence of thick and rigid cell walls (George and Burke 1977;Quamme et al 1982;George 1983;Ashworth and Abeles 1984;Wisniewski et al 1991a). However, it has recently been pointed out that the mechanisms of deep supercooling, especially the mechanism by which supercooling capability of XPCs in many trees changes from -10 to -60°C depending on latitudinal and seasonal environmental temperature changes, are difficult to explain only by physical isolation of water in XPCs (Fujikawa and Kuroda 2000;Fujikawa et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In regards to deep supercooling of xylem tissues, it has been previously demonstrated that the structure of the pit membrane portion of the cell wall affects whether or not xylem ray parenchyma cells exhibit deep supercooling (Wisniewski et al 1987(Wisniewski et al , 1991Wisniewski and Davis 1989). Furthermore, the data indicate that pectins may play a role in defining the porosity and permeability of the pit membrane of xylem parenchyma.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the distribution of pectins and/or the role of pectins in determining the freezing response of deep supercooled plant tissues has been determined through the use of pectinase-rich enzyme preparations (Wisniewski et al 1991 b), the use of calcium chelating agents (Wisniewski et al 1991 a), or the use of generalized histological stains (Czaninski 1977;Schaffer and Wisniewski 1989). In Wisniewski et al (1991a, b), extraction of pectic material resulted in a significant shift of the low-temperature exotherm (LTE) to warmer temperatures or a complete loss of the LTE.…”
Section: Introductionmentioning
confidence: 99%